High-ionic-conductivity lithium ion battery diaphragm and preparation method thereof
By using slurry of thin-layer MXene and crown ether modified graphene solution in lithium-ion battery separators, the problems of low liquid absorption and ionic conductivity of the existing separators are solved, and the cycle life and safety performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411572995.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-27
AI Technical Summary
The liquid absorption and ionic conductivity of existing lithium battery separators are low, resulting in insufficient cycle life and safety performance of the battery, making it difficult to meet the needs of faster discharge efficiency and longer cycle life.
Using a slurry including thin layer MXene solution and crown ether modified graphene solution, a rich ion channel is generated by combining dibenzo-18-crown-6 with graphene oxide and N,N-dimethyl Acetamide is mixed, applied evenly to the surface of the substrate and dried in vacuum to prepare a lithium-ion battery separator with high ionic conductivity.
It significantly improves the liquid absorbance and ionic conductivity of the separator, enhances the safety performance and circulation performance of the battery, and solves the problems of low liquid absorbance and low ionic conductivity of the traditional separator.
Smart Images

Figure BDA0005121011620000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, in particular to a high ion conductivity lithium ion battery separator and a preparation method thereof. Background Art
[0002] As an important energy storage device, lithium batteries are widely used in various electronic devices. The performance of lithium batteries, including their energy density, cycle life and safety, depends largely on the performance of lithium battery separators. Lithium battery separators are thin films placed between the positive and negative electrodes of the battery. Their main function is to prevent the positive and negative electrodes from physically contacting each other while allowing lithium ions to pass through. The performance of the separator, including its electrolyte absorption and retention rate, compatibility with the electrolyte and ionic conductivity, directly affects the performance and safety of lithium batteries. In particular, as current power batteries pursue faster discharge efficiency and longer cycle life, separators with strong ionic conductivity can improve the output power and charge and discharge efficiency of the battery. In addition, the use of separators with strong ionic conductivity can reduce the thermal runaway problem of the battery and improve the safety performance of the battery.
[0003] In order to overcome the defects of the prior art, the present invention provides a high ionic conductivity lithium ion battery separator and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a lithium ion battery separator with high ionic conductivity and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A high ion conductivity lithium ion battery separator comprises a substrate and a slurry coated on both sides of the substrate, wherein the slurry comprises a thin layer MXene solution, a crown ether modified graphene solution, and an N,N-dimethylacetamide solution.
[0007] More optimally, the volume ratio of the thin layer MXene solution and the crown ether modified graphene solution is 1:(1-3).
[0008] More optimally, the preparation process of the crown ether modified graphene solution is: mix the graphene oxide aqueous solution and the N,N-dimethylformamide solution, then add DB18C6-2NH2 and continue the reaction at 85-90°C for 24-30 hours. After the reaction is completed, centrifuge and remove excess DB18C6-2NH2 to obtain the crown ether modified graphene solution.
[0009] The preparation process of DB18C6-2NH2 is as follows: dissolving dibenzo-18-crown-6 (DB18C6) in a mixture of dichloromethane and acetic acid, stirring for 1-2 hours, then dropping a mixture of acetic acid and nitric acid, stirring at 50-60°C for 24-30 hours, filtering and washing with methanol after the reaction to obtain DB18C6-2NO2; mixing DB18C6-2NO2, Pd / C catalyst, 1,4-benzoquinone and anhydrous ethanol, The reaction was heated at 100-120° C. under a nitrogen atmosphere for 1-2 hours, and hydrazine hydrate was added to continue the reaction for 48-55 hours. After the reaction was completed, DB18C6-2NH2 was obtained by filtration, impurity removal, and solvent evaporation. The contents of the components of DB18C6-2NH2 were as follows: 5-7 parts of DB18C6-2NO2, 0.05-0.07 parts of Pd / C catalyst, 52-60 parts of 1,4-benzoquinone, 15-25 parts of anhydrous ethanol, and 10-12 parts of hydrazine hydrate, in parts by mass.
[0010] More optimally, the concentration of the graphene oxide aqueous solution is 10-12 mg / mL, the mass fraction of DB18C6-2NH2 is 20-25wt%, and the concentration of the crown ether modified graphene solution is 12-15 mg / mL.
[0011] The optimal preparation process of thin-layer MXene solution is as follows: LiF and hydrochloric acid are mixed, stirred thoroughly, and then MAX-Ti3C2T is slowly added. x , continue the reaction at 35-40°C for 24-30 hours, after the reaction is completed, centrifuge, remove the upper acid solution, wash the precipitate, and ultrasonicate, repeat the above post-reaction treatment steps until the pH of the upper liquid is 6.0-6.5 to obtain a multilayer MXene solution; mix the multilayer MXene solution and ethanol, then ultrasonicate, centrifuge, recover the precipitate, and concentrate to obtain a thin layer MXene solution.
[0012] More optimally, LiF, MAX-Ti3C2T x The mass volume ratio of the multilayer MXene solution to ethanol is 1:1:(20-25); the mass fraction of the hydrochloric acid is 36-38wt%; the weight ratio of the multilayer MXene solution to ethanol is (1.0-1.2):200; the concentration of the thin layer MXene solution is 12-15mg / mL.
[0013] A method for preparing a high ionic conductivity lithium-ion battery separator comprises mixing a thin layer MXene solution and a crown ether modified graphene solution, adding an N,N-dimethylacetamide solution, and fully stirring to obtain a slurry; the slurry is evenly coated on both sides of a substrate, and vacuum dried to obtain a finished product.
[0014] More optimally, the substrate can be any one of a polyethylene porous substrate, a polypropylene substrate, and a polyester substrate; the substrate thickness is 7 μm; and the coating thickness on each side is 2-3 μm.
[0015] Beneficial effects of the present invention:
[0016] The present invention prepares a DB18C6-2NH2 material by adding dibenzo-18-crown-6, dichloromethane, acetic acid, nitric acid, Pd / C catalyst, 1,4-benzoquinone, anhydrous ethanol and hydrazine hydrate. Then, the DB18C6-2NH2 material is used to modify the graphene oxide aqueous solution to obtain a crown ether modified graphene solution. By adding LiF, hydrochloric acid, MAX-Ti3C2T x , ethanol, to obtain a thin layer MXene solution. The crown ether modified graphene ether solution, the thin layer MXene solution and the N,N-dimethylacetamide solution are mixed to obtain a slurry; the slurry is evenly coated on the surfaces of both sides of the substrate, and a finished lithium ion battery separator is obtained after vacuum drying. The present invention prepares a lithium ion battery separator with high liquid absorption rate and high ionic conductivity.
[0017] The present invention is characterized in that dibenzo-18-crown-6 is a macrocyclic crown ether (CE). Crown ether has a strong attraction to lithium ions due to its unique three-dimensional structure, and can generate abundant ion channels after combining with graphene oxide. In addition, since both graphene oxide and MXenes materials have high electrical conductivity, the shortcomings of low liquid absorption rate and low ion conductivity of existing polyethylene diaphragms can be overcome, the liquid absorption rate and ion conductivity of the diaphragm can be greatly improved, and the safety performance and cycle performance of the battery can be improved. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Source of raw materials:
[0020] Graphene oxide, provided by Shanghai Aladdin Biochemical Technology Co., Ltd., with a particle size of <20um; MAX-Ti3C2T x , provided by Jilin Yiyi Technology Co., Ltd., model number is YY201753LS; by mass, one portion is 1g.
[0021] Example 1: Step 1: Dissolve 3 g of dibenzo-18-crown-6 (DB18C6) in a mixture of 80 mL of dichloromethane and 10 mL of 36 wt% acetic acid, stir thoroughly for 1 h, then drop 5 mL of a mixture of acetic acid and 2 mL of nitric acid, stir and react at 50°C for 24 h, filter and wash with methanol after the reaction to obtain DB18C6-2NO2; mix 5 g of DB18C6-2NO2, 0.05 g of Pd / C catalyst, 40 mL of 1,4-benzoquinone and 20 mL of anhydrous ethanol, heat and react at 100°C under a nitrogen atmosphere for 1 h, then add 10 mL of hydrazine hydrate and continue the reaction for 48 h, filter, remove impurities and evaporate the solvent after the reaction to obtain DB18C6-2NH2;
[0022] A 10 mg / mL graphene oxide aqueous solution and an N,N-dimethylformamide solution were mixed, and then 20 wt% DB18C6-2NH2 was added and reacted at 85°C for 24 h. After the reaction was completed, the excess DB18C6-2NH2 was removed by centrifugation to obtain a 12 mg / mL crown ether modified graphene solution, which was stored for later use;
[0023] Step 2: Mix 1g LiF and 20mL 36wt% hydrochloric acid, stir thoroughly, and then slowly add 1g MAX-Ti3C2T x , continue the reaction at 35°C for 24 hours, centrifuge at 3500rpm for 30 minutes after the reaction, remove the upper acid solution, wash the precipitate, sonicate, and centrifuge at 3500rpm for 30 minutes, repeat the above post-reaction treatment steps until the pH of the upper liquid is 6 to obtain a multilayer MXene solution; mix the multilayer MXene solution and ethanol, and the weight ratio of the multilayer MXene solution to ethanol is 1:200; then sonicate for 1 hour, centrifuge at 10000rpm for 1 hour, recover the precipitate, and concentrate to obtain a 12 mg / mL thin layer MXene solution, which is stored for later use;
[0024] Step 3: Mix the thin layer MXene solution and the crown ether modified graphene solution, then add N,N-dimethylacetamide solution and stir thoroughly to obtain a slurry; the volume ratio of the thin layer MXene solution and the crown ether modified graphene solution is 1:1; the slurry is evenly coated on the surface of both sides of a polyethylene porous substrate with a thickness of 7μm, and vacuum dried to obtain a finished product; the coating thickness on each side is 2μm.
[0025] Example 2: Changing the volume ratio of thin layer MXene solution and crown ether modified graphene solution to 1:2
[0026] Step 1: Dissolve 3g of dibenzo-18-crown-6 (DB18C6) in a mixture of 80mL of dichloromethane and 10mL of 36wt% acetic acid, stir thoroughly for 1h, then drop 5mL of a mixture of acetic acid and 2mL of nitric acid, stir and react at 50°C for 24h, filter and wash with methanol after the reaction to obtain DB18C6-2NO2; mix 5g of DB18C6-2NO2, 0.05g of Pd / C catalyst, 40mL of 1,4-benzoquinone and 20mL of anhydrous ethanol, heat and react at 100°C under a nitrogen atmosphere for 1h, then add 10mL of hydrazine hydrate and continue the reaction for 48h, filter, remove impurities and evaporate the solvent after the reaction to obtain DB18C6-2NH2;
[0027] A 10 mg / mL graphene oxide aqueous solution and an N,N-dimethylformamide solution were mixed, and then 20 wt% DB18C6-2NH2 was added and reacted at 85°C for 24 h. After the reaction was completed, the excess DB18C6-2NH2 was removed by centrifugation to obtain a 12 mg / mL crown ether modified graphene solution, which was stored for later use;
[0028] Step 2: Mix 1g LiF and 20mL 36wt% hydrochloric acid, stir thoroughly, and then slowly add 1g MAX-Ti3C2T x , continue the reaction at 35°C for 24 hours, centrifuge at 3500rpm for 30 minutes after the reaction, remove the upper acid solution, wash the precipitate, ultrasonicate for 10 minutes, centrifuge at 3500rpm for 30 minutes, repeat the above post-reaction treatment steps until the pH of the upper liquid is 6 to obtain a multilayer MXene solution; mix the multilayer MXene solution and ethanol, the weight ratio of the multilayer MXene solution to ethanol is 1:200; ultrasonicate for 1 hour, centrifuge at 10000rpm for 1 hour, recover the precipitate, concentrate, and obtain a 12 mg / mL thin layer MXene solution, which is stored for later use;
[0029] Step 3: Mix the thin layer MXene solution and the crown ether modified graphene solution, then add N,N-dimethylacetamide solution and stir thoroughly to obtain a slurry; the volume ratio of the thin layer MXene solution and the crown ether modified graphene solution is 1:2; the slurry is evenly coated on the surface of both sides of a polyethylene porous substrate with a thickness of 7μm, and vacuum dried to obtain a finished product; the coating thickness on each side is 2μm.
[0030] Example 3: Changing the volume ratio of thin layer MXene solution and crown ether modified graphene solution to 1:3
[0031] Step 1: Dissolve 3g of dibenzo-18-crown-6 (DB18C6) in a mixture of 80mL of dichloromethane and 10mL of 36wt% acetic acid, stir thoroughly for 1h, then drop 5mL of a mixture of acetic acid and 2mL of nitric acid, stir and react at 50°C for 24h, filter and wash with methanol after the reaction to obtain DB18C6-2NO2; mix 5g of DB18C6-2NO2, 0.05g of Pd / C catalyst, 40mL of 1,4-benzoquinone and 20mL of anhydrous ethanol, heat and react at 100°C under a nitrogen atmosphere for 1h, then add 10mL of hydrazine hydrate and continue the reaction for 48h, filter, remove impurities and evaporate the solvent after the reaction to obtain DB18C6-2NH2;
[0032] A 10 mg / mL graphene oxide aqueous solution and an N,N-dimethylformamide solution were mixed, and then 20 wt% DB18C6-2NH2 was added and reacted at 85°C for 24 h. After the reaction was completed, the excess DB18C6-2NH2 was removed by centrifugation to obtain a 12 mg / mL crown ether modified graphene solution, which was stored for later use;
[0033] Step 2: Mix 1g LiF and 20mL 36wt% hydrochloric acid, stir thoroughly, and then slowly add 1g MAX-Ti3C2T x , continue the reaction at 35°C for 24 hours, centrifuge at 3500rpm for 30 minutes after the reaction, remove the upper acid solution, wash the precipitate, ultrasonicate for 10 minutes, centrifuge at 3500rpm for 30 minutes, repeat the above post-reaction treatment steps until the pH of the upper liquid is 6 to obtain a multilayer MXene solution; mix the multilayer MXene solution and ethanol, the weight ratio of the multilayer MXene solution to ethanol is 1:200; ultrasonicate for 1 hour, centrifuge at 10000rpm for 1 hour, recover the precipitate, concentrate, and obtain a 12 mg / mL thin layer MXene solution, which is stored for later use;
[0034] Step 3: Mix the thin layer MXene solution and the crown ether modified graphene solution, then add N,N-dimethylacetamide solution and stir thoroughly to obtain a slurry; the volume ratio of the thin layer MXene solution and the crown ether modified graphene solution is 1:3; the slurry is evenly coated on the surface of both sides of a polyethylene porous substrate with a thickness of 7μm, and vacuum dried to obtain a finished product; the coating thickness on each side is 2μm.
[0035] Comparative Example 1: The preparation step of the thin layer MXene solution is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Dissolve 3g of dibenzo-18-crown-6 (DB18C6) in a mixture of 80mL of dichloromethane and 10mL of 36wt% acetic acid, stir thoroughly for 1h, then drop 5mL of a mixture of acetic acid and 2mL of nitric acid, stir and react at 50°C for 24h, filter and wash with methanol after the reaction to obtain DB18C6-2NO2; mix 5g of DB18C6-2NO2, 0.05g of Pd / C catalyst, 40mL of 1,4-benzoquinone and 20mL of anhydrous ethanol, heat at 100°C for 1h under a nitrogen atmosphere, add 10mL of hydrazine hydrate and continue the reaction for 48h, filter, remove impurities and evaporate the solvent after the reaction to obtain DB18C6-2NH2;
[0036] A 10 mg / mL graphene oxide aqueous solution and an N,N-dimethylformamide solution were mixed, and then 20 wt% DB18C6-2NH2 was added and reacted at 85°C for 24 h. After the reaction was completed, the excess DB18C6-2NH2 was removed by centrifugation to obtain a 12 mg / mL crown ether modified graphene solution, which was stored for later use;
[0037] Step 2: Mix the crown ether modified graphene solution and the N,N-dimethylacetamide solution, and stir them thoroughly to obtain a slurry; evenly apply the slurry to the surfaces of both sides of a polyethylene porous substrate with a thickness of 7 μm, and obtain a finished product after vacuum drying; the coating thickness on each side is 2 μm.
[0038] Comparative Example 2: The commercially available 7 um polyethylene porous substrate was directly used.
[0039] Detection test:
[0040] Contact angle test: Under the conditions of temperature of 25°C and relative humidity of 50%, the contact angle was tested using a contact angle measuring instrument model TBU100 (manufactured by Dataphysics, Germany). The EC / DMC (v:v=1:1) mixed solvent was slowly dripped onto the surface of the finished film prepared by the present invention. After dripping for 60 seconds, the wetting contact angle of the mixed solution was measured. The contact angles were measured at three points on the film, and the average of the three was used as the contact angle.
[0041] Liquid absorption test (EU): The finished membrane prepared by the present invention was cut into a circular diaphragm with a diameter of 19 mm, and the initial mass w0 was weighed after being fully dried under vacuum conditions. Then, the membrane was immersed in a mixed solvent of EC / DMC (v:v=1:1) for 24 h, the diaphragm was taken out, the electrolyte on the membrane surface was wiped dry and the mass wi was weighed, and then the mass w0 was measured according to the formula Calculate the liquid absorption rate.
[0042] Liquid retention rate test (ER): After the membrane is completely saturated with electrolyte, the membrane is placed in a desiccator at 50°C for 2 hours. The weight of the membrane is measured after 120 minutes, and the ER is obtained by the following formula: ER (%) = 100% - (WS-WD) / WS × 100%, where WD is the weight of the soaked membrane after drying, and WS is the weight of the wet membrane.
[0043] Ionic conductivity: The conductivity of the diaphragm is measured using an electrochemical workstation with a test frequency range of 0.001Hz-105Hz. The conductivity is then calculated using the formula σ=d / RbA, where σ is the conductivity of the diaphragm, d is the thickness of the diaphragm, Rb is the bulk resistance of the diaphragm, and A is the effective area of contact between the diaphragm and the electrode. The results are shown in the following table:
[0044]
[0045] Conclusion: The absorption capacity and wettability of the separator to the electrolyte directly affect the ion transport and interfacial impedance in the battery. Insufficient electrolyte will lead to increased internal resistance and decreased cycle performance, ultimately affecting the service life of the battery. The performance of the separator is characterized by testing the contact angle, liquid absorption rate (EU) and liquid retention rate (ER).
[0046] Contact angle analysis: Compared with the contact angle of the untreated PE separator (Comparative Example 2) (50.3°), the contact angle of the GO-CE coated separator is 27.5°, and after the introduction of MXene, the contact angle of the modified separator is significantly reduced to <20°. This shows that the introduction of GO-CE and MXene greatly enhances the affinity of the traditional PE separator to the electrolyte.
[0047] Liquid absorption analysis: The liquid absorption of comparative example 2 was 68.5%, which was significantly enhanced by 105.3% after GO-CE coating. This is due to the dense and well-organized graphene oxide coating, which has a strong affinity for electrolytes. When MXene was introduced, the liquid absorption of examples 1-3 reached 196.2%, 210.5% and 205.4%, respectively, which is much higher than that of the separator coated with GO-CE alone.
[0048] Analysis of liquid retention rate and ion conductivity: The ER of Examples 1-3 and Comparative Example 2 is much higher than that of the pure PE diaphragm, especially the ER of Example 2 is 5.15 times that of Comparative Example 2, showing a strong electrolyte retention rate. At the same time, through the analysis of the ionic conductivity test in the table, it can be seen that after coating with MXene and GO-CE, it shows better ion conductivity, which is much higher than the uncoated PE diaphragm. The reason for the analysis is: after inserting CE molecules and MXene inside and between graphene oxide layers, these molecules successfully optimize the spacing between graphene oxide nanosheet layers, so that the electrolyte is better absorbed and retained in the ion screening membrane channels. These characteristics are conducive to the development of power batteries with battery charging cycles that are as stable and efficient as possible.
[0049] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0050] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high ionic conductivity lithium ion battery separator, characterized in that: It includes a substrate and a slurry coated on both sides of the substrate, wherein the slurry includes a thin layer MXene solution, a crown ether modified graphene solution, and an N,N-dimethylacetamide solution.
2. A high ionic conductivity lithium ion battery separator according to claim 1, characterized in that: The volume ratio of the thin layer MXene solution and the crown ether modified graphene solution is 1:(1-3).
3. A high ionic conductivity lithium ion battery separator according to claim 1, characterized in that: The preparation process of the crown ether modified graphene solution is as follows: the graphene oxide aqueous solution and the N,N-dimethylformamide solution are mixed, DB18C6-2NH2 is added, and the reaction is continued at 85-90°C for 24-30 hours. After the reaction is completed, the crown ether modified graphene solution is obtained by centrifugation and removal of excess DB18C6-2NH2.
4. A high ionic conductivity lithium ion battery separator according to claim 3, characterized in that: The preparation process of DB18C6-2NH2 is as follows: dissolve dibenzo-18-crown-6 (DB18C6) in a mixture of dichloromethane and acetic acid, stir thoroughly for 1-2 hours, then dropwise add a mixture of acetic acid and nitric acid, stir and react at 50-60°C for 24-30 hours, filter and wash with methanol after the reaction to obtain DB18C6-2NO2; mix DB18C6-2NO2, Pd / C catalyst, 1,4-benzoquinone and anhydrous ethanol, and precipitate under nitrogen gas. The reaction was heated at 100-120°C under an atmosphere of 400-500 °C for 1-2 hours, and hydrazine hydrate was added to continue the reaction for 48-55 hours. After the reaction was completed, DB18C6-2NH2 was obtained by filtration, impurity removal and solvent evaporation. The contents of the components of DB18C6-2NH2 were as follows: 5-7 parts of DB18C6-2NO2, 0.05-0.07 parts of Pd / C catalyst, 52-60 parts of 1,4-benzoquinone, 15-25 parts of anhydrous ethanol and 10-12 parts of hydrazine hydrate, in parts by mass.
5. A high ionic conductivity lithium ion battery separator according to claim 3, characterized in that: The concentration of the graphene oxide aqueous solution is 10-12 mg / mL, the mass fraction of DB18C6-2NH2 is 20-25 wt %, and the concentration of the crown ether modified graphene solution is 12-15 mg / mL.
6. A high ionic conductivity lithium ion battery separator according to claim 1, characterized in that: The preparation process of thin-layer MXene solution is as follows: LiF and hydrochloric acid are mixed, stirred thoroughly, and then MAX-Ti3C2T is slowly added. x , continue the reaction at 35-40°C for 24-30 hours, after the reaction is completed, centrifuge, remove the upper acid solution, wash the precipitate, and ultrasonicate, repeat the above post-reaction treatment steps until the pH of the upper liquid is 6.0-6.5 to obtain a multilayer MXene solution; mix the multilayer MXene solution and ethanol, then ultrasonicate, centrifuge, recover the precipitate, and concentrate to obtain a thin layer MXene solution.
7. A high ionic conductivity lithium ion battery separator according to claim 6, characterized in that: LiF、MAX-Ti3C2T x The mass volume ratio of the multilayer MXene solution to ethanol is 1:1:(20-25); the mass fraction of the hydrochloric acid is 36-38wt%; the weight ratio of the multilayer MXene solution to ethanol is (1.0-1.2):200; the concentration of the thin layer MXene solution is 12-15mg / mL.
8. A method for preparing a high ionic conductivity lithium ion battery separator, characterized in that: The thin layer MXene solution and the crown ether modified graphene solution are mixed, and then N,N-dimethylacetamide solution is added and stirred thoroughly to obtain a slurry; the slurry is evenly coated on the surfaces of both sides of the substrate, and vacuum dried to obtain a finished product.
9. The method for preparing a high ionic conductivity lithium ion battery separator according to claim 8, characterized in that: The substrate may be any one of a polyethylene porous substrate, a polypropylene substrate, and a polyester substrate; the substrate thickness is 7 μm; and the coating thickness on each side is 2-3 μm.
10. Use of the lithium ion battery separator according to any one of claims 1 to 7 in a lithium ion battery.
